Mutational Landscape for Indian Hereditary Breast and Ovarian Cancer Cohort Suggests Need for Identifying Population Specific Genes and Biomarkers for Screening - Kadri, Mohammed Shaad N.; Patel, Komal M.; Bhargava, Poonam A.; Shah, Franky D.; Badgujar, Nutan V.; Tarapara, Bhoomi V.; Patel, Prabhudas S.; Shaikh, Mohammed Inayatullah; Shah, Krati; Patel, Apurva; Pandya, Shashank; Vora, Hemangini; et al. (Frontiers in Oncology, 2021)
Background: Breast and Ovarian cancers are the most prevalent cancers and one of the leading causes of death in Indian women. The healthcare burden of breast and ovarian cancers and the rise in mortality rate is worrying and stresses the need for early detection and treatment. Methods: We performed amplicon sequencing of 144 cases who had breast/ovarian cancer or had an indication of the disease using our custom designed gene panel consisting of 18 genes, that are associated with high to moderate risk of breast and ovarian cancers. Variants were called using Torrent Variant Caller and were annotated using ThermoFisher’s Ion Reporter software. Classification of variants and their clinical significance were identified by searching the variants against ClinVar database. Results: From a total of 144 cases, we were able to detect pathogenic mutations in 41/144 cases. Majority of pathogenic mutations (28/41) were detected in BRCA1 gene, while (7/41) pathogenic mutations were detected in BRCA2 gene, whereas, (2/41) pathogenic mutations were detected in TP53 gene and (1/41) pathogenic mutations were detected in AR, BRIP1, PALB2 and ATM genes respectively. So, BRCA genes contributed 85.36% of pathogenic mutations whereas, nonBRCA genes contributed 14.64% of pathogenic mutations. We were also able to detect 30 VUS which were predicted to be damaging by in silico prediction tools. Conclusion: Early detection of cancers in Indian population can be done by genetic screening using customized multi-gene panels. Indications of our findings show that in Indian population, apart from the common BRCA genes, there are other genes that are also responsible for the disease. High frequency mutations detected in the study and variants of uncertain significance predicted to be damaging by in silico pathogenicity prediction tools can be potential biomarkers of hereditary breast and ovarian cancer in Indian HBOC patients.